2021
DOI: 10.1002/bbb.2269
|View full text |Cite
|
Sign up to set email alerts
|

Cellulosic glycols: an integrated process concept for lignocellulose pretreatment and hydrogenolysis

Abstract: Lignocellulose is the most abundant source of saccharides and it is therefore a promising feedstock for glycols, such as ethylene-glycol, via catalytic hydrogenolysis of the polysaccharides that it contains. However, this catalytic hydrogenolysis step is hampered by the presence of lignin and other biomass contaminants, such as ash, which need to be removed in a pretreatment step. We propose an organosolv-like pre-treatment that can delignify and de-ash lignocellulose to a level that allows it to be upgraded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Note that water leaching is rather ineffective for the removal of divalent ions such as calcium as was previously shown. 26 This mild pretreatment was more effective in removing calcium and magnesium than the high severity pretreatments PT-A (ethanol−water, 50/50, 200 °C, 3 h) and PT-B (70 wt % acetic acid in water, 180 °C, 1 h) reported in our previous work, 12 whose solid residues had a combined calcium and magnesium content of 9 and 3.2 mmol per kg of biomass, respectively. On the contrary, acid leaching only removes inorganics and water-soluble extractives, whereas lignin removal might be imperative for long-term operation.…”
Section: Addition Of Ashmentioning
confidence: 83%
See 2 more Smart Citations
“…Note that water leaching is rather ineffective for the removal of divalent ions such as calcium as was previously shown. 26 This mild pretreatment was more effective in removing calcium and magnesium than the high severity pretreatments PT-A (ethanol−water, 50/50, 200 °C, 3 h) and PT-B (70 wt % acetic acid in water, 180 °C, 1 h) reported in our previous work, 12 whose solid residues had a combined calcium and magnesium content of 9 and 3.2 mmol per kg of biomass, respectively. On the contrary, acid leaching only removes inorganics and water-soluble extractives, whereas lignin removal might be imperative for long-term operation.…”
Section: Addition Of Ashmentioning
confidence: 83%
“… a Quantification was performed at least in duplicate. b Data previously published in refs. , c Recalculated from untreated feedstocks. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that water leaching is rather ineffective for the removal of divalent ions such as calcium [115] . Acid leaching was more effective in removing calcium and magnesium than the high severity pretreatments PT-A (Ethanol-water, 50/50, 200 • C, 3 h) and PT-B (70 wt.% Acetic acid in water, 180 • C, 1 h) reported in Chapter 7 [111] , whose solid residues had a combined calcium and magnesium content of 9 and 3.2 mmol per kg of biomass respectively. However, these high severity pretreatments also remove lignin.…”
Section: Wo X Consumption -Beyond Camentioning
confidence: 87%
“…For industrial operation the catalyst consumption should be minimized and preferably stay below 1 kg Catalyst / tonne product [89] . Under the assumption that one mole of cation precipitates one mole of WO x , we derived that the maximum allowable divalent cation content of the biomass feedstock can be 4 mmol per kg biomass (Chapter 7) [111] . This assumption was validated in this chapter as we showed that calcium precipitates with tungstate in an equimolar ratio.…”
Section: Wo X Consumption -Beyond Camentioning
confidence: 99%